SWOT Analysis as a Strategy for Madrasah Principals in Realizing Academic Madrasah - Norman, Efrita; Paramansyah, Arman; Utami, Widaya; Aminah, Siti (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to understand the strategy of madrasah principals in realizing academic madrasah through SWOT analysis at Madrasah Aliyah Negeri 2 Bogor City. This study uses a qualitative case study approach, where the researcher uses interviews, observations, and documentation to collect data. The data analysis was carried out by referring to the Miles and Huberman concept, namely data collection, data reduction, data presentation, and concluding. The results showed that the head of MAN 2 Bogor City had implemented his strategic management very well in realizing Academic Madrasahs. This is indicated by the success of the madrasah target achievement programs made by the madrasah principal. In addition, it can also be seen from the SWOT analysis diagram through internal and external factors described in the IFE and EFE matrices. Through this matrix, it was found that MAN 2 Bogor City is in quadrant I, meaning that the head of MAN 2 Bogor City are advised to use a progressive strategy by utilizing the internal strengths of the madrasa to take advantage of the external opportunities of the madrasa to achieve the goal of becoming an Academic Madrasah.